2006
DOI: 10.1074/jbc.m508019200
|View full text |Cite
|
Sign up to set email alerts
|

Feedback of the Kinesin-1 Neck-linker Position on the Catalytic Site

Abstract: Kinesin-1 motor proteins step along microtubules by a mechanism in which the heads cycle through microtubule-bound and unbound states in an interlaced fashion. An important contribution to head-head coordination arises from the action of the neck-linker that docks onto the core motor domain upon ATP binding. We show here that the docked neck-linker not only guides the microtubule-unbound head to the next microtubule binding site but also signals its position to the head to which it is attached. Cross-linking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
8
15
0
Order By: Relevance
“…It is in accordance with an experimental study showing that both the neck linker and ATP bind to a motor head (31). This coupling between the neck linker and the ATP binding site was also observed by other research groups (32,33). In this work, we further identified how this coupling was regulated by external loading forces.…”
Section: Molecular Origin Of the Weak Susceptibility Of Kinesin Velocsupporting
confidence: 77%
“…It is in accordance with an experimental study showing that both the neck linker and ATP bind to a motor head (31). This coupling between the neck linker and the ATP binding site was also observed by other research groups (32,33). In this work, we further identified how this coupling was regulated by external loading forces.…”
Section: Molecular Origin Of the Weak Susceptibility Of Kinesin Velocsupporting
confidence: 77%
“…However, there are likely other conformations of the NL that position it close to the MD but that are different from this docked state that has been visualized by ATP-like crystal structures. One such conformation was previously induced by selective cross-linking, which artificially induced NL immobilization (via designed disulfide bonds) and led to the complete inhibition of kinetic activity for monomeric as well as dimeric kinesin constructs (17). Our inactivation-with concurrent loss of microtubule binding-could thus be similar to the decreased microtubule affinity observed previously when the NL was artificially held in place close to the MD (17).…”
Section: Discussionsupporting
confidence: 62%
“…Instead, we hypothesize that a smaller change occurs. Recent work highlighted the position of the NL domain relative to the rest of the head as changing during the enzymatic cycle and as being important for alteration of the MT binding affinity (16,17). Thus, kinesin inactivation might reflect a conformational change that alters the position/conformation of the NL relative to the head.…”
Section: Inactive Kinesin Undergoes a Conformational Change Resulting Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Many members of the kinesin and myosin motor families are double-headed with the 2 heads joined by a double-helical coiled coil. In the case of the molecular motor kinesin, various studies have shown that for processive movement along microtubular tracks, a communication between the 2 heads through mechanical strain is essential (1)(2)(3)(4). A recent study by Yildiz et al (5) has shown that transmission of the strain generated by neck-linker docking can be critically affected by inserting artificial peptides between neck-linker and neck, thus introducing slack into the connection between the 2 heads.…”
mentioning
confidence: 99%